Incubation of turkey eggs: effect of disinfection method and breeder age - Medina R., Stefanie (2023)
The aim of the study was to analyze the influence of the egg disinfection method and breeder age on incubation parameters in a turkey breeder farm. Two disinfection methods were evaluated: T1, fumigation with formaldehyde gas (8 g/m3) and T2, wetting with a glutaraldehyde + quaternary ammonium solution (4 ml/l of water), which were applied to hatching eggs from two batches of B.U.T breed turkeys from 51 to 57 weeks of age. A completely randomized block design with a 2x7 factorial arrangement was used. Hatchability, birth, mortality and discard parameters were determined. The disinfection method influenced the culling of hatched poults (p<0.05), where T1 achieved less culling (3%) compared to T2 (3.8%). No significant differences were observed in hatchability, births and mortality between disinfection methods. The increase in the age of the breeder generated a significant decrease (p<0.05) in hatchability and culling and increased (p<0.05) the percentage of mortality but did not influence births. It is concluded that the disinfection method only influenced the culling rate, while the age of breeders influenced hatchability, mortality and culling, but not poult births.